ANALYSIS OF FACTORS AFFECTING CUSTOMER SATISFACTION AND CUSTOMER RETENTION ON E-COMMERCE - Nuraini, Dewi; Hendratmi, Achsania (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2021)
This study aims to analyze the factors that influence consumer retention on the e-commerce website Hijup. This study uses website quality, brand image, and Islamic physical attributes as factors that will shape customer satisfaction which in turn will affect customer retention. This research is quantitative research using two types of data, namely primary data and secondary data. Primary data is obtained by distributing online questionnaires through social media, and secondary data is obtained from books, journals, papers, websites, etc. The number of respondents used in this study were 185 respondents from Hijup consumers who had bought online more than once. This study uses the type of SEM-PLS analysis with SMARTPLS 3.0 software tools. This study shows that website quality and brand image affect customer satisfaction. Moreover, customer satisfaction is able to moderate website quality and brand image on customer retention on the Hijup website, but Islamic physical attributes have a negative relationship with customer satisfaction.